A cascade approach to sustainable agriculture: From mushroom mycelium to lettuce harvest - Ré, Beatriz Bruno [UNESP]; Vieira Junior, Wagner Gonçalves [UNESP]; Postiguel, Rafael Barros [UNESP]; Alves, Lucas da Silva [UNESP]; Caitano, Cinthia Elen Cardoso [UNESP]; Freitas, Marcos Antônio da Silva [UNESP]; Zied, Diego Cunha [UNESP] (Elsevier, 2024)
Sustainable agriculture involves adopting best practices in food production to promote environmental and economic sustainability. Its implementation primarily aims to utilise organic residues to increase yield, diversify production, and reduce costs. In this context, the objective of this study was to investigate different substrates for Hypsizygus ulmarius production and, from its residual substrate, to develop formulations for lettuce seedling growth and subsequent greenhouse cultivation. For mushroom production, substrates were prepared from sawdust with the addition of wheat bran, rice bran, soybean meal, and calcite, resulting in four distinct substrate formulations. The spent mushroom substrate (SMS), obtained at the end of cultivation, was used for lettuce seedling production along with the commercial substrate Carolina Soil® and the soil conditioner BacSol®. The top five formulations were selected for transplanting in the greenhouse. Regarding mushroom production, substrates with higher carbon/nitrogen ratios, around 66: 1, resulted in higher yields. For seedling production, SMS showed lower efficiency compared to the commercial substrate Carolina Soil®, which also benefited from the addition of the soil conditioner BacSol®. However, after transplanting lettuce seedlings, the formulation containing SMS showed superior results in almost all evaluated parameters. Therefore, we concluded that despite the inefficiency of using H. ulmarius SMS for lettuce seedling production, it favours the establishment of seedlings in greenhouse cultivation environments.
Keywords: Agricultural waste management; Food production cycle; Horticulture; Mushroom production; Reuse of organic material